A Wayfarer in a Land of the Free: American Sufism in the Age of DIY Religiosity - Yusak, Nailil Muna (Universitas Islam Negeri (UIN) Walisongo Semarang, Indonesia, 2019)
This paper observes theological shift towards a personalized spirituality of Muslim religiosity in America. In the face of global resurgence of Islamic movement and its ambitious call towards purification, personalized form of Islam is strongly criticized to be deviant and a mere practice of heresy. Islamic mysticism or commonly known as Sufism gained more popularity in modern America for its stress on God’s mercy over exclusive legalism in understanding cosmic law and the divine consequences. Over the year, it has proven its catalytic role for a more peaceful interreligious understanding on account to reflexivity and cosmopolitan consciousness. Drawing from a recent scholarship by Ulrich Beck on individualized religion, this paper explores; process of individualization of religion in forming modern American religious experience and the socio-cultural relevance of Sufism in shaping contemporary religious relation of Islam in America. Data utilized in this research draws upon interviews and observational fieldworks in the East Coast America.